1998
DOI: 10.1001/archinte.158.21.2349
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Benign Prostatic Hyperplasia

Abstract: Our results indicate that more physically active men have a lower frequency of lower urinary tract symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 33 publications
8
66
2
2
Order By: Relevance
“…[8][9][10][11] Inverse association emerged for both occupational and recreational PA and was consistently found in different strata of selected covariates. The strongest association emerged with occupational or recreational PA in young adulthood (~50% of risk reduction), but some protection was also found for high PA levels at ages 50-59 years (one-third reduction).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…[8][9][10][11] Inverse association emerged for both occupational and recreational PA and was consistently found in different strata of selected covariates. The strongest association emerged with occupational or recreational PA in young adulthood (~50% of risk reduction), but some protection was also found for high PA levels at ages 50-59 years (one-third reduction).…”
Section: Discussionmentioning
confidence: 83%
“…24 An alternative hypothesis suggested that sedentary lifestyle decreases the sympathetic nervous system activity, which is associated with increased prostate smooth muscle tone and severity of lower urinary tract symptoms. 11 As urological complications of BPH may lead to mobility reduction and may discourage recreational activities, an inverse causation cannot be totally ruled out. 25 However, a remarkable consistency emerged in the direction and strength of the associa- A possible weakness of the present study is the lack of a wellaccepted definition of BPH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Similar report by steve A. Kaplan showed that a few things may cause lower urinary tract symptoms which could be urologic and non urologic states; mediators that increases obstructive urinary symptoms, obesity, regular alcohol consumption, and elevated blood pressure all could lead to benign prostatic hyperplasia. 7,8 This is supported too in Aruna v. sarma et al studies were they alluded that black 9 , obesity 10 ,diabetes mellitus 11 ,high levels of alcohol consumption 12 and physical inactivity 13 increases risk of BPH development. The obstructive symptoms includes the urinary hesistancy, delay in initiating micturition, intermittency, involuntary interruption of voiding, weak urinary stream, straining to void, a sensation of incomplete emptying, and terminal dribbling.…”
Section: Imentioning
confidence: 87%